Nasopharyngeal and Adenoid Colonization by Haemophilus influenzae and Haemophilus parainfluenzae in Children Undergoing Adenoidectomy and the Ability of Bacterial Isolates to Biofilm Production. Issue 18 (May 2015) - Kosikowska, Urszula; Korona-Głowniak, Izabela; Niedzielski, Artur; Malm, Anna; Dessein., Rodrigue
<x xml:space="preserve">Abstract</x> Abstract Haemophili are pathogenic or opportunistic bacteria often colonizing the upper respiratory tract mucosa. The prevalence of Haemophilus influenzae (with serotypes distribution), and H. parainfluenzae in the nasopharynx and/or the adenoid core in children with recurrent pharyngotonsillitis undergoing adenoidectomy was assessed. Haemophili isolates were investigated for their ability to biofilm production. Nasopharyngeal swabs and the adenoid core were collected from 164 children who underwent adenoidectomy (2–5 years old). Bacteria were identified by the standard methods. Serotyping of H. influenzae was performed using polyclonal and monoclonal antisera. Biofilm formation was detected spectrophotometrically using 96-well microplates and 0.1% crystal violet. Ninety seven percent (159/164) children who underwent adenoidectomy were colonized by Haemophilus spp. The adenoid core was colonized in 99.4% (158/159) children, whereas the nasopharynx in 47.2% (75/159) children (P < 0.0001). In 32% (51/159) children only encapsulated (typeable) isolates of H. influenzae were identified, in 22.6% (36/159) children only (nonencapsulated) H. influenzae NTHi (nonencapsulated) isolates were present, whereas 7.5% (12/159) children were colonized by both types. 14.5% (23/159) children were colonized by untypeable (rough) H. influenzae. In 22% (35/159) children H. influenzae serotype d was isolated. Totally, 192 isolates of H. influenzae, 96 isolates of H. parainfluenzae and 14 isolates of other Haemophilus spp. were selected. In 20.1% (32/159) children 2 or 3 phenotypically different isolates of the same species (H. influenzae or H. parainfluenzae) or serotypes (H. influenzae) were identified in 1 child. 67.2% (129/192) isolates of H. influenzae, 56.3% (54/96) isolates of H. parainfluenzae and 85.7% (12/14) isolates of other Haemophilus spp. were positive for biofilm production. Statistically significant differences (P = 0.0029) among H. parainfluenzae biofilmproducers and nonproducers in the adenoid core and the nasopharynx were detected. H. influenzae and H. parainfluenzae carriage rate was comparatively higher in the adenoid core than that in the nasopharynx in children undergoing adenoidectomy, suggesting that their involvement in chronic adenoiditis. The growth in the biofilm seems to be an important feature of haemophili colonizing the upper respiratory tract responsible for their persistence.